Inclusive Education: Factors Influencing Atypical Academic Pathways of Youth in Portugal - de Oliveira Rodrigues, Marta; Loureiro, Armando; Marques da Silva, Sofia (Calitatea Vieții, 2025)
This research, framed theoretically within studies on school success, aims to generate knowledge about the successful academic pathways of students at risk of school failure and social exclusion in compulsory education. Employing a qualitative approach, a multi-case study was conducted in a municipality located in the north-eastern region of Portugal, within the framework of two national education interventions: the Priority Intervention Educational Territories (TEIP) and the Choices Programme, aimed to promote school success and social inclusion in formal and non-formal educational contexts, respectively. The qualitative data involved content analysis of biographical interviews with children and young people. The findings reveal how maternal involvement, teacher recognition, and non-formal educational activities play a decisive role in reshaping atypical academic pathways, and in supporting academic success among disadvantaged youth. These results offer insights for the design of educational practices and policies that strengthen socio-educational support systems to improve school outcomes and educational quality.